Review on the toxic effect of fluorine and lead on lichen metabolism - Ouahiba Benhamada; Nabila Benhamada; Essaid Leghouchi (International Journal of Secondary Metabolite, 2024)
Thanks to their ability to absorb large amounts of trace elements from the atmosphere, lichens are widely used as bioaccumulators and bioindicators of air pollution. Among air pollutants, heavy metals represented by lead are the most important contributors to the deterioration of ecosystems. Fluorine is prevalent in a wide range of environmental matrices, even in trace amounts, and is one of the most phytotoxic halogens to plants. When lichens are exposed to air pollution, they frequently undergo structural, morphological and physiological alterations, and exhibit several coping strategies to combat and tolerate stressful situations. This manuscript presents general information about lichens, fluorine, and lead as well as the toxic effect of these two air pollutants on lichens, and the means of combat used by lichens to respond to fluorine and lead-induced stress.